Natural oak regeneration in response to selective cutting - Keith, Samuel (2020)
The natural regeneration of sessile oak (Quercus petraea (Matt.) L.) and pedunculate oak (Quercus robur L.) is largely uncertain across central Europe and Scandinavia. Both species are key components of unique biodiversity niches, but have been supressed under modern forestry and land use practices. During the last century, large areas of semi-natural mixed forests have re-established on agricultural land abandoned from traditional farming, however these forests are often overgrown and form dark environments. Environmental schemes, such as the ‘TransForest’ project, have identified such areas as potential sites for the restoration of temperate deciduous woodland. Selective cutting is seen as a management option that can favour the natural regeneration of temperate broadleaf tree species such as oak which in the long run, contributes to the achievement of an array of biodiversity goals. The process of selective cutting is founded upon the principle that oak regenerates best in light rich environments and the targeted removal of shade dominant tree species e.g. Norway spruce, can contribute to the creation of lighter forest environments. This study analyses the effectiveness of selective cuttings on the natural regeneration of oak in a series of mixed forest stands across southern Sweden as well as the relationship between oak seedling density and light availability. The stem density of oak seedlings in different height classes is used as a response indicator to cuttings and hemispherical photographs have provided measurements of the understory light transmittance. The association between oak seedling density and light availability is found to be most significant for stems under 20 cm indicating that selective cuttings have had a positive impact on oak recruitment. The short time span of this experiment is suggested as a reason that improved regeneration is not yet realised in the taller height classes. Browsing by wild ungulates is also discussed as posing a significant threat to oak establishment and should be paid due consideration in restoration efforts.